The glyceraldehyde-3-phosphate dehydrogenase GapDH of Corynebacterium diphtheriae is redox-controlled by protein S-mycothiolation under oxidative stress - Hillion, Melanie; Hell, Rüdiger; Wirtz, Markus (Scientific reports, 2017)
Mycothiol (MSH) is the major low molecular weight (LMW) thiol in Actinomycetes and functions in post-translational thiol-modification by protein S-mycothiolation as emerging thiol-protection and redox-regulatory mechanism. Here, we have used shotgun-proteomics to identify 26 S-mycothiolated proteins in the pathogen Corynebacterium diphtheriae DSM43989 under hypochlorite stress that are involved in energy metabolism, amino acid and nucleotide biosynthesis, antioxidant functions and translation. The glyceraldehyde-3-phosphate dehydrogenase (GapDH) represents the most abundant S-mycothiolated protein that was modified at its active site Cys153 in vivo. Exposure of purified GapDH to H2O2 and NaOCl resulted in irreversible inactivation due to overoxidation of the active site in vitro. Treatment of GapDH with H2O2 or NaOCl in the presence of MSH resulted in S-mycothiolation and reversible GapDH inactivation in vitro which was faster compared to the overoxidation pathway. Reactivation of S-mycothiolated GapDH could be catalyzed by both, the Trx and the Mrx1 pathways in vitro, but demycothiolation by Mrx1 was faster compared to Trx. In summary, we show here that S-mycothiolation can function in redox-regulation and protection of the GapDH active site against overoxidation in C. diphtheriae which can be reversed by both, the Mrx1 and Trx pathways.
Published online: 10 July 2017
Gesehen am 22.06.2018